Rancang Bangun Sistem Pengelolaan Laundry menggunakan Metode Waterfall - Abdul Hafiz Syaputra; Ucuk Darussalam; Winarsih Winarsih (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2021)
Laundry is one of the businesses engaged in laundry and clothes ironing services that are starting to develop. This laundry business provides kilogram washing services, including washing and drying services, dry cleaning and ironing, washing bed covers, washing thin blankets to thick blankets. Laundry management is done manually and simply so that mistakes often occur due to human errors in recording information and not a few missing records and quite a long recording time. Therefore, in the development of information technology today, one of the efforts to overcome this problem is to create a website-based laundry application. The purpose of this study is to build a website-based laundry application to facilitate businesses in the field of laundry, namely laundry using the programming language PHP, HTML, CSS, JavaScript, and MySQL database as data storage. The system is built in stages using the waterfall method which consists of the stages of analysis, design, implementation, and system testing. The result of this research is a website-based laundry application that can facilitate each employee's job in handling customers as well as customers getting convenience in transactions for using laundry services.